Different responses to hypobaria between spider mites and a predatory mite. Issue 7 (3rd October 2017) - Wang, C.-H.; Hosomi, A.; Suzuki, T.; Ullah, M. S.; Gotoh, T.
ABSTRACT: Spider mites are a quarantine pest for different agricultural products imported to Japan, which may require phytosanitary treatments. To develop an environmental-friendly physical method to control agricultural pests, with minimal harm to natural enemies, we evaluated the effect of hypobaria (reduced atmospheric pressure) on three pest spider mites ( Tetranychus urticae, T. kanzawai, Panonychus citri ) and their natural enemy, the predatory mite Neoseiulus californicus . None of the spider mite eggs hatched when exposed to 17 kPa (lower partial pressure of oxygen, pO2  ≈ 3.5 kPa) at 25°C or 30°C for 24 h. The hatchability of N. californicus eggs was slightly reduced when the eggs were exposed to hypobaria at 30°C for 24 h. However, N. californicus adult females were more susceptible to hypobaria than females of the three species of spider mites. Adult survival of T. urticae and P. citri was significantly reduced by exposure to hypobaria at 30°C for 12 or 24 h, while adult survival of N. californicus was significantly reduced at 20°C, 25°C, and 30°C for ≥12, ≥12, and ≥6 h, respectively. For most species in most of the exposures, the adult survivabilities could be recovered by supplying water during the treatment. The exception was N. californicus when exposed to hypobaria at 30°C for 24 h. These results suggest that hypobaric-induced desiccation rather than hypoxia (pO2  ≈ 3.5 kPa) causes the mortality of adult females and that hypobaric treatments can be useful for selectively controlling spider mite eggs for phytosanitary treatment of several commercially important fresh commodities.